Study on Compressive Strength of Self-Compacting Concrete (SCC) Based on Fly Ash. Issue 2 (April 2021) - Yu, Guoping; Chen, Ru; Luo, Changtai; Xie, Banghua
Abstract: Fly ash (FA) has a good effect on the fluidity and strength of self-compacting concrete (SCC). The experimental research method was adopted, equipped with C35 self-compacting concrete, w/c =0.4 and FA content a =0%∼40%. The compressive strength of SCC was studied for T=3d, 7d, 14d, 28d, 60d. It is found that FA has a great impact on the compressive strength of SCC. With the continuous addition of FA, the strength of SCC increases at first, and then decreases. When a =25%, the compressive strength of SCC is best, reaching 47.3 MPa. As with ordinary concrete, the strength of SCC varies with curing time. When T=7d-14d, SCC strength increases less.